Evolution of technological paradigms and economic foundations of the transformation of production systems in the construction industry - Korytko, Dmytrii (Ways to Improve Construction Efficiency, 2025)
The purpose of the article is to analyze the evolution of technological paradigms and to determine the economic foundations of the transformation of production systems in the construction industry under conditions of technological change and digital transformation. The research focuses on identifying the key technological, economic, and institutional factors that influence the modernization of production systems and determine the structural transformation of the construction sector. The methodological framework of the study is based on the principles of evolutionary economics and the theory of techno-economic paradigms. The research applies systemic, dialectical, and institutional approaches to analyze technological change and structural transformation of production systems. Methods of scientific abstraction, comparative analysis, synthesis, and institutional analysis were used to examine the development patterns of the construction industry and the impact of digital technologies on production processes. The results of the research demonstrate that the evolution of technological paradigms plays a decisive role in shaping the transformation of production systems in the construction industry. Historically, the development of construction production has been characterized by a relatively slow pace of technological change due to the fragmented structure of the sector, project-based production processes, and significant regulatory constraints. However, the emergence of digital technologies and the concept of Construction 4.0 has created new opportunities for technological modernization. The integration of Building Information Modeling (BIM), Internet of Things (IoT), artificial intelligence, robotics, and additive manufacturing enables the formation of integrated digital ecosystems that connect the stages of design, construction, and operation of buildings. These technologies significantly improve coordination between project participants, reduce construction errors, optimize resource management, and increase productivity in the sector. The scientific novelty of the research lies in the conceptualization of the transformation of production systems in the construction industry through the prism of technological paradigm evolution. The study integrates the theoretical provisions of evolutionary economics with contemporary approaches to digital transformation and Construction 4.0. It also systematizes the technological, economic, and institutional factors that determine the modernization of production systems in the construction industry. The practical significance of the study lies in the possibility of applying its results to the development of strategies for technological modernization of the construction industry. The research findings may be used by policymakers, industry regulators, and construction companies to design effective mechanisms for implementing digital technologies, improving productivity, and enhancing the competitiveness of the sector. The results may also contribute to the development of institutional mechanisms aimed at supporting innovation and digital transformation in the construction industry. The research confirms that the evolution of technological paradigms significantly influences the economic foundations of the transformation of production systems in the construction industry. Digitalization, automation, and the integration of advanced technologies create new opportunities for improving efficiency and productivity in the sector. The successful implementation of these technological transformations requires coordinated technological, organizational, and institutional changes aimed at ensuring sustainable development and increasing the innovative capacity of the construction industry.